Permanent magnet motor technology : design and application. - Gieras, Jacek F., ....- (Boca Raton : CRC, 2010)
With an ever growing amount of human enterprise and activity dependent on motors, there is the increasing need to train students and engineers in the area of modern electrical motors and drives, including their control and simulation. Reflecting the latest innovations in the development of PM motors for electromechanical drives, this new edition presents equations and calculations to determine and evaluate system performance, efficiency, reliability, and cost. It also explores modern computer-aided design of PM motors. A wealth of exercises help reinforce the principles covered.